Advancing periodontitis microbiome research: integrating design, analysis, and technology - Yibing Han; Pei-Hui Ding (Frontiers in Cellular and Infection Microbiology)
Periodontitis, a chronic inflammatory disease affecting 20%-50% of adults worldwide, is driven by polymicrobial synergy and dysbiosis. Despite numerous studies on the oral microbiota in periodontitis, significant heterogeneity exists between findings, posing challenges for treatment strategies. To understand the sources of this variability and establish standardized protocols, we reviewed the literature to identify potential factors contributing to these discrepancies. We found most studies focus on microbial communities in periodontal pockets, with fewer investigating microbial composition within gingival tissue. Research indicates that bacterial communities in gingival tissue exist as biofilms, potentially serving as reservoirs for persistent infection. Therefore, further exploration of the microbiome within periodontal tissues is needed, which may offer new insights for treatment strategies. Metatranscriptomics provides valuable insights into gene expression patterns of the oral microbiota, enabling the exploration of microbial activity at a functional level. Previous studies revealed that most upregulated virulence factors in periodontitis originate from species not traditionally considered major periodontal pathogens. However, current studies have not fully identified or revealed the functional changes in key symbiotic microbes in periodontitis. We reviewed the analytical paradigms of metatranscriptomics and found that current analysis is largely limited to assessing functional changes in known periodontal pathogens, highlighting the need for a functional-driven approach. Beyond the limitations of current analytical paradigms, the metatranscriptomics also has inherent constraints. We suggested integrating emerging high-throughput microbial sequencing technologies with functional-driven analytical strategies to provide a more comprehensive and higher-resolution insight for microbiome reconstruction in periodontitis.